The failed promise : Reconstruction, Frederick Douglass, and the impeachment of Andrew Johnson - Levine, Robert S. (Robert Steven), 1953- (W. W. Norton & Company, 2021)
"The absorbing narrative of Frederick Douglass's heated struggle with President Andrew Johnson reveals a new perspective on Reconstruction's demise. When Andrew Johnson rose to the presidency after Abraham Lincoln's assassination, African Americans were optimistic that Johnson would pursue aggressive federal policies for Black equality. Just a year earlier, Johnson had cast himself as a "Moses" for the Black community. Frederick Douglass, the country's most influential Black leader, increasingly doubted the president was sincere in supporting Black citizenship. In a dramatic meeting between Johnson and a Black delegation at the White House, the president and Douglass came to verbal blows over the fate of Reconstruction. Their animosity only grew as Johnson sought to undermine Reconstruction and conciliate leaders of the former Confederate states. Robert S. Levine grippingly recounts the conflicts that led to Johnson's impeachment from the perspective of Douglass and the wider Black community. In counterpointing the lives and careers of Douglass and Johnson, Levine offers a fresh vision of the lost promise and dire failure of Reconstruction"--